Siste istids glasiasjons- og deglasiasjonshistorie i øvre Sølndalen, Alvdal vestfjell - Gjærde, Helen (The University of Bergen, 2015)
The Weichselian glacial history of Norway, and particularly the Last Glacial Maximum (LGM, 18- 20 ka) is the main focus of this master thesis. The thesis focuses on creating a map of an area in Sølndalen, Hedmark county. The chosen area is located in central Southern Norway, a region known for cold-based ice conditions and large ice-dammed lakes. Preservation of landforms in the area suggests that the ice sheet was cold- based, with low erosive abilities. A glaciation history based on field work and some dating results is created with six main phases of deglaciation. Dating of sediments from Optically Stimulated Luminescence (OSL) in comparison with mapped field data, indicates a smaller vertical extent of the LGM ice sheet. Afterwards a new build-up of ice occurred, about 14 ka. Exposure ages from a cirque glacier at the mountain Storsølnkletten show that the glacier probably did not exist until the end of the glaciation period (about 10 ka). A detailed map of relevant features was created, based on extensive field work in Sølndalen. publishedVersion GEO350 MASV-GEOG